EduCode: Development of a Mobile-based Coding Educational Game for Children - Taufiqurrohman Taufiqurrohman; Hoiriyah Hoiriyah; Moh. Badri Tamam; Rofiuddin Rofiuddin (SISTEMASI, 2026)
The rapid advancement of digital technology has significantly transformed the educational landscape. However, its utilization as an interactive learning medium for children remains limited. At the same time, the integration of Computational Thinking into Indonesia's Merdeka Curriculum highlights the importance of introducing coding at an early age. Nevertheless, many children continue to face difficulties in understanding fundamental programming logic due to the limited availability of engaging and effective learning media. This study aims to develop and evaluate EduCode, an educational game designed to provide an interactive and enjoyable coding learning experience for children. The game was developed using the Game Development Life Cycle (GDLC) methodology, which consists of six phases: initiation, pre-production, production, testing, beta, and release. EduCode was implemented using the Flutter framework and the Dart programming language. System functionality was evaluated through Black-Box Testing, while usability was assessed using a Likert-scale questionnaire administered to elementary school students as the end users. The usability evaluation yielded an average score of 89.80%, which falls into the "Very Good" category. These findings indicate that EduCode demonstrates a high level of usability in terms of ease of use, user comfort, and interface design. Therefore, EduCode is considered a highly suitable alternative learning medium for enhancing children's engagement and motivation in learning coding while improving their Computational Thinking skills at the elementary school level.